Wheelchair users accessibality to Shah Alam’s lake garden / Ahmad Akmal Mohd Zikri and Mayamin Yuhaniz - Mohd Zikri, Ahmad Akmal; Yuhaniz, Mayamin (2019)
Rehabilitation according to Person with Disability Act 2008, refersto a process aimed at enabling person who are born with disability to attain and maintain their full physical, mental, social and vocational ability and full inclusion and participation in all aspect of life. (Person with Disability Act 2008, 2014). Integration of wheelchair bound individual into the society requires accessibility to any building or public spaces, including public park. This study assessed the wheelchair user’s accessibility of Shah Alam’s Lake Garden. The grade of the ramp in the parking area are measured and calculated. Accessibility was determined by comparing the collected information with The Malaysian Standard MS 1184 2002. Only four out of six (66.7%) carpark studied that have ramp. One out of six (16.7%) ramp that are studied actually complies to the maximum grade of ramp which is 1:12, as highlighted by The Malaysian Standard MS 1184.